COMPARATIVE REPELLENCY DURATION OF CITRONELLA OIL LOTION (Cymbopogon nardus L.) BETWEEN Culex sp. WITH Aedes sp. AS LYMPHATIC FILARIASIS VECTOR - Rita Tjokropranoto (Indonesian Journal of Pharmacy, 2014)
Lymphatic filariasis is a mosquito borne disease, transmitted by mosquitoes such as Culex, Anopheles, Aedes, Mansonia. Filariasis infection resulting in disability. The important method to avoid being bitten from mosquitoes is by using a repellent. The purpose of this study were to compare repellency duration of citronella oil lotion against Culex sp. to Aedes sp. and to compare its repellency duration to N,N-diethyl-m-toluamide (DEET). Laboratory experimental design was conducted at each of five men as subjects using five randomly treatments: 20%, 40% citronella oil lotion (COL), lotion base (negative control), 12.5% DEET lotion with one-day time lag. Repellency duration, since the forearm was inserted into the cage until first mosquito land, was assessed using female Culex sp. and Aedes sp, according to modification of Fradin and Day method. Repellency duration was analyzed using one-way ANOVA, Tukey HSD followed by paired t-test level of significance with a=0.05 level of significance at p<0.05. There were highly significant differences (p<0.01) between average repellency duration (minute) of 20%, 40%, 80% COL against Culex sp. and 40%, 80% against Aedes sp. compared to 12.5% DEET. It was concluded that citronella oil lotion was more effective to Culex sp. than that of Aedes sp. Nevertheless the potency of citronella oil lotion was weaker than 12.5% DEET.Key word: lotion citronelle oil, Culex sp., Aedes sp., Filariasis